TARGETING TYPE I INTERFERON SIGNALING IN SYSTEMIC LUPUS ERYTHEMATOSUS: CLINICAL AND SAFETY PERSPECTIVES ON ANIFROLUMAB THERAPY - Sara Zahra Omidi; Daria Valipur Kolti; Jerzy Klimas; Barbara Anna Olędzka; Wiktoria Mazepa; Małgorzata Olędzka; Michał Piątkiewicz; Kaja Pruszkowska; Zofia Rogowska (International Journal of Innovative Technologies in Social Science, 2026)
Anifrolumab is a fully human IgG1 monoclonal antibody targeting the IFNAR1 subunit of the type I interferon receptor. By inhibiting the JAK-STAT signaling pathway and suppressing interferon-stimulated gene expression, anifrolumab represents a targeted therapy based on disease pathophysiology. The drug has been approved as an add-on treatment for adult patients with moderate to severe systemic lupus erythematosus particularly in patients in whom standard therapies such as systemic glucocorticoids and hydroxychloroquine have failed to achieve the desired outcomes. The efficacy of anifrolumab has been assessed in several randomized clinical trials, which demonstrated a significant reduction in disease activity, decreased rates of disease flares, and improvement in cutaneous and musculoskeletal manifestations. Another clinically relevant outcome was the possibility to reduce glucocorticosteroid doses. Further analyses also suggest a beneficial effect of anifrolumab in lupus nephritis and indicate its superiority over standard therapy. Anifrolumab has demonstrated a favorable safety profile, with no significant increase in the risk of serious adverse events or opportunistic infections. The most frequently reported adverse events were upper respiratory tract infections as well as varicella and herpes zoster infections. In Poland, anifrolumab is registered exclusively for the treatment of adults with moderate to severe systemic lupus erythematosus as an adjunct to standard therapy. However, evidence from clinical trials and case series suggest the potential for broader application of this drug in dermatology in the coming years. In the future, anifrolumab may also be considered a therapeutic option in refractory cases of cutaneous lupus erythematosus.